Mini-implant supported canine retraction with micro-osteoperforation: A split-mouth randomized clinical trial - Sivarajan, Saritha; Doss, Jennifer Geraldine; Papageorgiou, Spyridon N.; Cobourne, Martyn T.; Wey, Mang Chek (E.H. Angle Education and Research Foundation, 2019)
Objectives: To investigate, using a split-mouth randomized clinical design, the effect of micro-osteoperforation (MOP) on mini-implant supported canine retraction using fixed appliances. Materials and Methods: Thirty subjects (seven males and 23 females) with a mean age of 22.2 (3.72) years were randomized into three canine retraction groups: Group 1 (MOP 4-weekly maxilla/ 8-weekly mandible; n = 10); Group 2 (MOP 8-weekly maxilla/12-weekly mandible; n = 10) and Group 3 (MOP 12-weekly maxilla/4-weekly mandible; n = 10) measured at 4-week intervals over 16 weeks. Subjects also completed pain (5-point Likert scale) and pain impact (Visual Analogue Scale) questionnaires. The primary outcome was the amount of canine retraction over 16 weeks at MOP (experimental) and non-MOP (control) sites. Results: Mean overall canine retraction was 4.16 (1.62) mm with MOP and 3.06 (1.64) mm without. After adjusting for differences between jaws, all MOP groups exhibited significantly higher canine distalization than the control group: 0.89 mm more (95% confidence interval [CI] = 0.19 to 1.59 mm; P =.01) in the MOP-4 group, 1.08 mm more (95% CI = 0.49 to 1.68 mm; P =.001) in the MOP-8 group and 1.33 mm more (95% CI = 0.55 to 2.10 mm; P =.002) in the MOP-12 group. All subjects reported pain associated with MOP with 60% classifying it as moderate and 15% severe. The main impact of this reported pain was related to chewing and speech. Conclusions: MOP can increase overall mini-implant supported canine retraction over a 16-week period of observation but this difference is unlikely to be clinically significant. © 2019 by The EH Angle Education and Research Foundation, Inc.